CHANGES IN OLDER ADULT FALLS, FALL INJURIES, AND FALL FATALITIES ACROSS THE UNITED STATES—2012–2016. (16th November 2018) - Burns, E; Kakara, R; Stevens, M; Bergen, G
Abstract: Falls are the leading cause of injury among adults aged 65 and older and cost 50 billion/year in medical expenditures. The age-adjusted rate of fatal falls increased 31% nationally and in most states during the past decade. However, the corresponding change in the prevalence of self-reported falls and fall injuries is unknown and has not been compared to the increasing fall fatality rate. Any increase in the prevalence of falls would translate to a greater burden to the healthcare system. Data from the 2012, 2014, and 2016 Behavioral Risk Factor Surveillance System were used to calculate fall and fall injury prevalence, controlling for age. Year-to-year differences in fall and fall injury prevalence were detected using two-sample t-tests. Data from Vital Statistics were used to calculate fall fatality rates and were age-adjusted with the 2000 U.S. Census. Joinpoint was used to determine significant change for fall fatalities from 2012–2016. State-specific estimates of fall and fall injury prevalence and fatality rates were compared to the national prevalence and rate using two-sample t-tests. From 2012–2016 the fall prevalence increased nationally and in nine states. The prevalence of fall injuries increased in five states and decreased in one but did not change nationally. The fall fatality rate increased nationally and in 17 states and decreased in 1 state. In 2016, only New Mexico had a higher prevalence of self-reported falls and fall injuries, and a higher rate of fall fatalities compared to the national average.